THE ARGUMENT ON A STUDENT’ THESIS OF DEPARTMENT OF ISLAMIC EDUCATION - Agustiningsih, Dheka Dwi; Permatasari, Andalusia Neneng; Alhamuddin, Alhamuddin (International Journal of Education, 2017)
This paper discusses the arguments found in a student’ academic writing, namely a thesis. It attempts to show how an argument is built in a student’s thesis in the Department of Islamic Education, Faculty of Tarbiyah and Education, Islamic University of Bandung by drawing upon the theory of Toulmin (2003). The results of this research show that verse, hadith, and exegesis become the starting point of the argument to be presented in the thesis. However, there is a discrepancy between the verses used as warrant’s claim and the data on the student’s thesis. Consequently, the argument becomes unstable because of the inconsistencies of argument elements. The implication of this research is concerned with the supervision process of a student’s thesis that should give more emphasis on how the student makes his or her arguments correctly.